Planning for the Development of a 40 kWp Off-Grid Centralized Solar Power Plant (SPP) on Insumbabi Island - Yusuf, Erwin; Jakariya; Subeno, Agus (Universitas Negeri Jakarta, 2025)
This study aims to design and evaluate a 40 kWp off‑grid centralized Solar Power Plant (SPP) to meet the electricity needs of two underserved villages on Insumbabi Island, Supiori Regency, Papua, Indonesia. A systematic planning and technical design process was conducted, comprising field surveys, satellite‑based solar potential analysis, load assessment, and system configuration. Performance simulations using photovoltaic (PV) Syst software indicate a daily energy output of 158.386 kWh, delivered by 216 PV modules and battery storage with two‑day autonomy. The system achieves an annual average production of 3.3–3.6 kWh/kWp/day. The maximum energy that can be produced by the solar panels reaches 67,661 kWh per year, with the highest monthly output of 6,194 kWh in August and the lowest of 4,992 kWh in February, a performance ratio (PR) of 0.602, and a solar fraction (SF) of 1.0. This confirms its capacity to fully meet local energy demands year‑round. The proposed design demonstrates high feasibility and offers a replicable model for off‑grid rural electrification projects in Indonesia.